2019
DOI: 10.31083/j.rcm.2019.01.53
|View full text |Cite
|
Sign up to set email alerts
|

Treatment models of cardiac rehabilitation in patients with coronary heart disease and related factors affecting patient compliance

Abstract: Coronary heart disease is a serious threat to human health. In China, medical care for the population has been focused on therapy with little follow-up of treated patients. The efficacy of therapy; however, is highly dependent on post-therapy recovery. Cardiac rehabilitation can significantly enhance patient physical strength and help delay and prevent the development of coronary atherosclerosis. Although the clinical significance of cardiac rehabilitation has been established, the compliance of patients is ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…Our study demonstrated higher level of non-adherence with secondary prevention medications in patients with CHD (60.0%) than was broadly consistent in the modern literature data [7,8,11,12]. This fact can be explained by the socioeconomic reasons, less informative strategies from the medical staff to the patients, especially general practitioners.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study demonstrated higher level of non-adherence with secondary prevention medications in patients with CHD (60.0%) than was broadly consistent in the modern literature data [7,8,11,12]. This fact can be explained by the socioeconomic reasons, less informative strategies from the medical staff to the patients, especially general practitioners.…”
Section: Discussionsupporting
confidence: 89%
“…Healthcare professionals should assess, elicit and explore patients' beliefs and experiences with their medications to help them make informed choices and decrease non-adherence. This requires the use of specific tools that can be deployed in clinical practice to explore and address barriers to proper medications usage [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Coronary heart disease is a disease caused by coronary artery stenosis or occlusion of myocardial ischemia, hypoxia, or necrosis. As the course of the disease increases, it can increase the incidence of chronic heart failure [ 1 ]. At present, the clinical treatment of coronary heart disease mainly focuses on reducing blood lipids, preventing risk factors, and symptomatic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of cardiovascular diseases has been on the rise annually with the onset of aging. In particular, coronary heart disease is becoming increasingly common (1,2). Although percutaneous coronary intervention (PCI) is a commonly used method to treat atherosclerotic coronary heart disease, postoperative restenosis occurs in a considerable proportion of angioplasty patients, leading to a reduction in the success rate of PCI treatment whilst increasing the risk of new cardiovascular complications (3).…”
Section: Introductionmentioning
confidence: 99%